Oil palm: its origins and cultivation in the African context - (:unkn) unknown (My University, 2025)
The history of oil palm in Africa is marked by an evolution from traditional exploitation to industrialization, influenced by colonial dynamics and global economic needs. Today, issues related to palm oil production include environmental sustainability and social justice for local communities. Having become the most widely used oil in the world and one of the least expensive due to its exceptional yields, palm oil is widely used in the agri-food industry.
Keywords: African Research